STUDENT PARTICIPATION IN EXTRA-CURRICULAR SCOUTING AND THE ENHANCEMENT OF DISCIPLINE A CORRELATIONAL STUDY IN PUBLIC VOCATIONAL SCHOOLS - Ali SURYADI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
This research aims to examine student extracurricular participation through scouting activities in relation to the level of discipline in Public Vocational High School East Jakarta City. Using quantitative approach, the researcher collected data from 364 student respondents by means of Likert scaled questionnaires. This study involved 12 vocational high schools in East Jakarta. To ensure the representativeness, the sample was proportionally randomized out of 6701 student population. Prior to data collection, the instruments were validated to 30 respondents. The study concluded that there was a moderate positive correlation between the level of student involvement and discipline at Public Vocational High School in East Jakarta.